Caracterización morfométrica y faneróptica del pato criollo (Cairina moschata domestica) - Altamirano Torres, Christopher Ronny (2025)
In the present investigation, 20 ducks were evaluated, equally distributed between the Coast (10) and the Sierra (10), analyzing morphometric and coloration variables. Regarding sex, a slight predominance of males (55%) over females (45%) was observed, although without significant differences. The general average weight was 2717.02 g, with higher values on the Coast (2825.88 g) than in the Sierra (2608.16 g), but without statistical differences. In the morphometric characteristics, significant differences were recorded in some variables. The head length was greater on the Coast (6.69 cm) compared to the Sierra (5.85 cm), while the head width did not show statistically relevant variations. In wing and body length, the specimens from the Coast were superior (48.40 cm and 47.20 cm) in comparison with those from the Sierra (42.35 cm and 29.80 cm), differences classified in distinct groups. Similarly, the abdominal perimeter was greater on the Coast (33.30 cm) than in the Sierra (29.60 cm), confirming the influence of geographical location on physical development. Regarding coloration, a marked difference was evident between regions. On the Coast, white and black plumage predominated (70%), followed by iridescent and marbled black, configuring a homogeneous population. In the Sierra, on the other hand, a greater chromatic diversity was observed with black and white (30%), gray (30%), brown with gray (20%), and white (20%). Something similar occurred in the color of the legs and eyes: on the Coast, yellow tones and light combinations predominated, while in the Sierra, darker variations stood out, such as brown eyes and yellow with gray legs. In summary, the results show that the geographical location significantly influences the morphometric characteristics and the chromatic diversity of the ducks, highlighting a greater corporal development and less variability on the Coast compared to a greater heterogeneity in the Sierra.